Imaging and clinical outcomes of COVID-19- vs. non-COVID-19-related cerebral venous thrombosis - Maxhuni, Toska; Doeppner, Thorsten R.; Braun, Tobias; Emde, Julia; Struffert, Tobias; Dembek, Thomas; Huttner, Hagen B.; Juenemann, Martin B.; Gerner, Stefan T. (Frontiers in Stroke, 2024)
Background Cerebral venous thrombosis (CVT) is a rare but serious subtype of stroke. Several studies have reported an increased incidence of CVT after either COVID-19 (CoV19) infection or vaccination; however, data on clinical characteristics, the radiological profiles, and the outcomes of these patients with CVT as the only severe symptom of a CoV19 infection or vaccination compared to patients with non-CoV19-related CVT are still scarce. Methods We performed a retrospective monocentric study over 10 years (January 2013–December 2022) that included consecutive patients with a confirmed diagnosis of CVT based on imaging of the cerebral venous system. Patients were categorized as CoV19 CVT (either due to infection or post-vaccination) or non-CoV19 CVT and compared regarding demographics, risk factors, clinical characteristics, and imaging findings as well as outcome (at discharge, at 6 months, and last follow-up). Furthermore, sub-analyses were performed to compare CoV19-infection-related-CVT and CoV19-vaccination-related-CVT patients. Results Overall, 122 patients with suspected CVT were identified. After excluding patients with missing data (n = 20) or missing imaging of the cerebral venous system (n = 31), 71 patients with confirmed CVT remained for the final analyses. Of those, 11 patients had CoV19 CVT (infection n = 3, vaccination n = 8), and 60 patients had non-CoV19-CVT. There were no differences regarding median age (CoV19: 40 [IQR: 22–70] vs. non-CoV19: 41 [IQR:27–64]) or percentage of female sex among both groups. A lower rate of CVT risk factors was observed in the CoV19 group but without significant differences. No patient with CoV19 CVT displayed impaired consciousness on presentation, and only 30% had focal neurological deficits compared to 51.7% in the control group. The rate of CVT-related intracranial hemorrhage and venous infarcts were 27.3% and 9.1%, respectively, in the CoV19 group and 30% and 16.7%, respectively, in the non-CoV19 group. The mortality rate at discharge was 9.1% in the CoV19-CVT group vs. 3.3% in the non-CoV19-CVT group, without differences in functional outcomes during the follow-up period. Sub-analyses comparing CoV19-infection-related CVT vs. CoV19-vaccination-related CVT patients revealed no significant differences in clinical, imaging, or treatment characteristics. Conclusion In this monocentric study, there was no signal for a worse severity of CoV19 CVT compared to non-CoV19 CVT regarding clinical characteristics, imaging profile, or outcomes in patients with CVT only. Larger observational data with sophisticated workups of CVT patients are needed to confirm our results.